The Linguistic Construction of Political Identity: the Case of Catalonia - Negro, Isabel (Círculo de Lingüística Aplicada a la Comunicación, 2024)
In the last decades much research has been carried out on discourse as a form of social practice from the Critical Discourse Analysis perspective. The Vienna school of CDA led by Wodak and her associates has developed a discourse-historical approach to discourse which investigates the linguistic construction of national identities through a method of description and analysis which posits three categories –topics, strategies and linguistic devices– employed in the construction, perpetuation, transformation and dismantling of nations and national identities. Following this approach, the present paper aims to analyse the linguistic construction of Catalonia’s present and political future in a corpus of public discourse fragments produced by Catalan pro-independence leaders and activists during the so-called Catalan crisis. The analysis reveals that the linguistic construction of the Catalan present and political future relies on constructive, justification and dismantling strategies that seek to support self-determination and construe Catalonia as an independent Republic.